1995
DOI: 10.1007/bf00187205
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation state and site selection of gold in (YBa2Cu3O7 ??)(1 ? x)Au x

Abstract: Recent experiments on the effect of Au substitution on the superconductivity of YBa2Cu307_~ (YBCO) have revealed that Au, unlike most other dopants, enhances the superconducting transition temperature, Tc, by ~ 2 K at 10 mole % Au. In the present study, X-ray photoelectron spectra, nominally of 4, 6, 8 and 10 mole% Au-doped YBCO, have been obtained. The Au spectra display a relatively intense peak which is the oxidized component associated with the Au 4f7/2 core level, and an additional component that is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The YBCO compound is one of the most studied and interesting HTS materials for applications. Doping studies have shown that the YBCO T C is always lowered except for doping with Au or Hg which increases T C by 2 K [24] and 10 K [25], respectively. In [25] Hg was introduced into YBCO during sintering by changing the composition of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The YBCO compound is one of the most studied and interesting HTS materials for applications. Doping studies have shown that the YBCO T C is always lowered except for doping with Au or Hg which increases T C by 2 K [24] and 10 K [25], respectively. In [25] Hg was introduced into YBCO during sintering by changing the composition of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33] (ii) Changing the composition and/or structure of the superconductors by the use of radiation of different energy content and nature realized with very different techniques. [34][35][36][37][38][39][40][41][42][43][44] (iii) Changing the composition and/or structure of the superconductors by annealing or post-annealing in different atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…The fine tuning (modification) of known superconductors can be roughly divided into three subgroups: (i) Changing the composition and/or structure of the superconductors by "doping" achieved during the synthesis itself. [29][30][31][32][33] (ii) Changing the composition and/or structure of the superconductors by the use of radiation of different energy content and nature realized with very different techniques. [34][35][36][37][38][39][40][41][42][43][44] (iii) Changing the composition and/or structure of the superconductors by annealing or post-annealing in different atmospheres.…”
Section: Introductionmentioning
confidence: 99%